2022
DOI: 10.1101/2022.12.30.522216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural populations in the language network differ in the size of their temporal receptive windows

Abstract: A left-lateralized network of frontal and temporal brain regions is specialized for language processing-spoken, written, or signed. Different regions of this 'language network' have all been shown to be sensitive to various forms of linguistic information, from combinatorial sentence structure to word meanings, to sub-lexical regularities. However, whether neural computations are the same across and within these different brain regions remains debated. Here, we examine responses during language processing reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 138 publications
(318 reference statements)
0
5
0
Order By: Relevance
“…As discussed earlier, there are good reasons to adopt this approach: the different regions of this network i) have similar functional response profiles, both with respect to their selectivity for language (e.g., 1315,17,18 ) and their responses to linguistic manipulations (e.g., 21,58 ), and ii) exhibit highly correlated time courses during naturalistic cognition paradigms (e.g., 59,60,83,11 ). However, some functional heterogeneity has been argued to exist within the language network (e.g., 162164,160,165,166 ). Future efforts using an approach like the one adopted here may discover functional differences within the language network (by searching for stimuli that would selectively drive particular regions within the network) as well as between the core LH language network and the RH homotopic areas and other language-responsive cortical, subcortical, and cerebellar areas.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, there are good reasons to adopt this approach: the different regions of this network i) have similar functional response profiles, both with respect to their selectivity for language (e.g., 1315,17,18 ) and their responses to linguistic manipulations (e.g., 21,58 ), and ii) exhibit highly correlated time courses during naturalistic cognition paradigms (e.g., 59,60,83,11 ). However, some functional heterogeneity has been argued to exist within the language network (e.g., 162164,160,165,166 ). Future efforts using an approach like the one adopted here may discover functional differences within the language network (by searching for stimuli that would selectively drive particular regions within the network) as well as between the core LH language network and the RH homotopic areas and other language-responsive cortical, subcortical, and cerebellar areas.…”
Section: Discussionmentioning
confidence: 99%
“…One constraint on this space of hypotheses has to do with the size of the language network’s temporal integration (or receptive) window (e.g., Lerner et al, 2011 ). In particular, previous work has shown that the temporal integration window of the language network is relatively short, on the order of a clause or sentence (e.g., Blank & Fedorenko, 2020 ; Lerner et al, 2011 ; Regev et al, 2022 ; Shain, Kean, et al, 2023 ). It is therefore likely that nonverbal meanings that the language system is concerned with have to do with individually described states or agent-patient interactions, but not longer-timescale representations like situation models whose construction can span long sequences of events ( Johnson-Laird, 1983 ; Loschky et al, 2020 ; Zwaan & Radvansky, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is engaged in language comprehension [32,33] and production [34] across different modalities and tasks. It supports language processing at the sub-lexical [35], lexical, and syntactic levels [36][37][38], it is also sensitive to the difficulty of language processing [39][40] and responds to differences between comprehension in native and non-native languages in polyglots [41].…”
Section: Speech Production In L2 As a Difficulty For Core Language Me...mentioning
confidence: 92%
“…It is engaged in language comprehension [32,33] and production [34] across different modalities and tasks. It supports language processing at the sub-lexical [35], lexical, and syntactic levels [3638], it is also sensitive to the difficulty of language processing [3940] and responds to differences between comprehension in native and non-native languages in polyglots [41]. What is more, the language network was shown to be sensitive to lexical access demands [34], and lexical access difficulty related to speaking in the L2 compared to the native language [42].…”
Section: Introductionmentioning
confidence: 99%